Departure to ruins in pre-Islamic poetry: A study in the semiotics of emotional and existential outcome - Al-Zomor, Amal Qasem Mohammed Melhi; Othman, Mohd AlaUddin; Salem, Elsayed Mohammed (Journal of Arabic Language Sciences and Literature, 2024)
Our research into the emotional and existential outcome is based on the underlying emotion that prompts the pre-Islamic self to leave for the ruins of the country and head there to observe it in its manifestations and changing conditions. The study aims to search for the self’s sense of the outcome after a state of emotion directed towards the target subject, in forming the final state represented by The evaluative level of emotion and judgment of standing and its effects based on the principle of rooting the idea of transience and immortality, in light of the approach to the semiotics of emotions. The study concluded that the emotional outcome of the departure to the ruins has an existential dimension that began with longing as a dominant emotion that represented the initial state tending to leave to it, and it was transformed by the impact of the home state. To sadness, then despair and worries that pushed the self to leave it as a final state of standing, It has been shown that fate is an existential fate, such that the combination of the self’s perceptual state and the evaluative judgment of the emotional state stopped the flow of longing as a tendency to communicate, and sadness over what was lost, especially in the stage of gray hair, revealed by the impact of the space of ruins and their fate in the self as a manifestation similar to it in loss, depletion, and absence, and like the eternity that was characterized by it. The remains of the homeland have an impact on the formation of her cognitive state of the outcome as a manifestation of her opposite.